Properties and Microstructure of Roller Compacted Concrete With High Volume Low Quality Fly Ash - Shuhua LIU; Qiaoling LI; Meijuan RAO; Lu WANG (Medžiagotyra, 2017)
The properties of roller compacted concrete (RCC) with high dosage low quality fly ash are investigated, including strength, elastic modulus, ultimate tensile strain, drying shrinkage, autogenous deformation and durability, meanwhile the microstructure of the same paste containing low quality fly ash and ground low quality fly ash are studied, too. The properties of RCC containing 60% or more ground fly ash meet the design requirement. The microstructure is also tested by using X-ray diffraction (XRD), scanning electron microscopy (SEM), thermogravimetry-differential thermal analysis (TG-DTA) and Mercury Intrusion Porosimetry (MIP). The results indicate that ground fly ash plays the role of active component besides the physical filling effect at early age, while after 90 days, the surface of the glass beads is erroded and a lot of calcium silicate hydrate and calcium hydroxide staggered as storied dense structure. Low quality fly ash can accelerate the formation of hydration products, resulting in higher degree of cement hydration and denser microstructure, while the hydration heat in total is reduced. At the age of 90 days, fly ash has significant chemical activity and the properties of RCC will be improved at the later stage. DOI: http://dx.doi.org/10.5755/j01.ms.23.3.16318